An ergonomic assessment among academic staff in higher learning institution - Elysia Tang, Tzi Yan (2025)
Work-related musculoskeletal Discomfort (WRMSDs) is prevalent among academic staff due to prolonged computer use, sedentary postures, and repetitive tasks. This study aims to determine the association between personal and ergonomic risk factors with reported WRMSDs among academic staff. A cross-sectional study was conducted with 100 academic staff. Data on personal and ergonomic risk factors, along with WRMSD symptoms, were collected using a socio-demographic questionnaire, the Rapid Office Strain Assessment (ROSA), and the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ). The results revealed a high prevalence of WRMSDs (90%), with the most affected regions being the lower back (86%), neck (86%), and right shoulder (88%). The average ROSA score was 6.02, indicating a high ergonomic risk. Significant associations (p < 0.05) were found between WRMSD prevalence and gender, age, work duration, service years, frequency of computer use, and ergonomic awareness. However, no significant association was observed between WRMSDs prevalence and ROSA rank category (χ²=0.208, P=0.648). These findings highlight the urgent need to address ergonomic issues in academic workplaces and raise awareness about mitigating WRMSDs. Collaboration among stakeholders is crucial to improving workplace ergonomics, raising awareness, and promoting preventive strategies are essential to reducing WRMSD risks and enhancing the well-being of academic staff.